Colonic epithelial cells are a major site of macrophage inflammatory protein 3α (MIP-3α) production in normal colon and inflammatory bowel disease. Issue 6 (1st December 2002) - Kwon, J H; Keates, S; Bassani, L; Mayer, L F; Keates, A C
Abstract : Background and aim: Macrophage inflammatory protein 3α (MIP-3α) is a recently described lymphocyte directed C-C chemokine expressed predominately at extralymphoid sites, including the intestine. The aim of this study was to determine whether colonic epithelial cells produce MIP-3α and whether its expression is upregulated in inflammatory bowel disease. Methods and results: We found that interleukin 1β and tumour necrosis factor α dose dependently stimulated MIP-3α production in Caco-2 and HT-29 intestinal epithelial cells. In cytokine treated Caco-2 and HT-29 cells, a significant increase in MIP-3α protein production was observed after three hours and continued for at least 24 hours. Analysis of colonic tissues by quantitative real time polymerase chain reaction and ELISA revealed significantly elevated MIP-3α mRNA levels (7.9-fold; p<0.05) and protein levels (8.9-fold; p<0.05) in Crohn's disease compared with controls or ulcerative colitis. MIP-3α immunoreactivity in normal colon and inflammatory bowel disease was principally associated with crypt and surface epithelial cells. Moreover, MIP-3α protein levels were elevated in primary epithelial cells isolated from patients with inflammatory bowel disease. Conclusions: These findings indicate that increased enterocyte MIP-3α production may play an important role in lymphocyte activation and recruitment to the colonic epithelium in Crohn's disease and ulcerative colitis.